Assessing the industrial PhD: Stakeholder insights - Katharina Grimm (OmniaScience, 2018)
Research and practice have called for a change in engineering education towards a more practice-oriented curricula to provide engineers with the skills they need for creating solutions for future challenges. While most studies address undergraduate programs, only little attention has been paid to graduate and post-graduate education. The Industrial PhD is expected to give PhD students on-the-job training to gain practically relevant and professional tacit knowledge and to enhance their set of soft skills. However, the training of practice-relevant methods and knowledge has so far been covered by alternative programs (e.g. traineeships), exclusively organized, financed and conducted by firms, and did not involve the responsibility of universities. Therefore, for the I.PhD, conflict between involved firms and universities can be expected. In order to analyze the potential of the Industrial PhD as an answer to the question of how to effectively make engineering education more practice-oriented, the present study analyses qualitative data on the experience of both industry and university actors with I.PhD programs. Questions on a) the motives and b) the perceived challenges allow valuable insights in the functionality of the I.PhD in terms of its success in its practical conduction.  The study results indicate a divergence in the perception of the general value of I.PhD program among both stakeholder groups. Major challenges can be identified, while existing work on PhD training and university-industry research cooperation (UIRC) allow the deduction of success-supporting factors, which can be believed to enhance the effectiveness of I.PhD programs for all parties.